THE ANALYSIS OF LOCUTION, ILLOCUTION, AND PERLOCUTION SPEECH ACTS IN MATA NAJWA TRANS 7 - Dea Riva Salsabila; Dasep Suprijadi (PROJECT (Professional Journal of English Education), 2021)
This research is entitled "The Analysis of Locution, Illocution, and Perlocution Speech Acts in Mata Najwa Trans 7". The purpose of this study was to analyze the forms of speech acts of locution, illocution, and perlocution found in the Mata Najwa event in Trans 7. This study used the speech act theory proposed by Searle. At the data collection stage, the documentation method was used. The stages of data analysis used the contextual method—the stage of presenting the results of data analysis used formal and informal methods. In the Mata Najwa event, three types of speech acts were found: locution, illocution, and perlocution. Two data are locution speech acts, two data are illocutionary, and two data are perlocution. Keywords:  Locution, Illocution, Perlocution, Mata Najwa, Speech Act